Evidences of Bedrock Forcing on Glacier Morphodynamics: A Case Study in Italian Alps - Dematteis, Niccolò; Giordan, Daniele; Perret, Paolo; Grab, Melchior; Maurer, Hansruedi; Troilo, Fabrizio (Frontiers in Earth Science, 2022)
It is well known that bedrock geometry influences glacier surface morphology. Nevertheless, in mountain glaciers, quantitative evidences are rare. In our research, we measured the ice thickness of the Planpincieux Glacier (North-west Italy), and detected the bedrock topography using ground-penetrating radar. Additionally, we obtained glacier morphology and kinematics by applying the techniques structure from motion and digital image correlation, respectively. Digital terrain analysis evidenced recurrent crevasses position that corresponded to bedrock steps. On average, since 2014, their positions varied between 6-14 m and were 40±8 m downstream of the bedrock steps. Bedrock and glacier topography presented out-of-phase correlated undulations that approximately fit a sinusoidal functions of different amplitude. Moreover, we show the morphological evolution of a large unstable sector whose thickness has remained approximately constant since 2014. Contrarily, ice thinning between 20 July and 8 September 2020 caused volume loss >30%. Since the damages provoked by potential failure depend primarily on the involved volume, this finding demonstrates that high-frequency morphology monitoring is essential for correct glacial hazard assessment.